Antimicrobial resistance patterns of Escherichia coli and Klebsiella pneumoniae isolated from patients with urinary tract infections: a prospective study from a tertiary care hospital in Hyderabad - Gandham, Pavani; Arumugam, Kumuda (International Journal of Research in Medical Sciences, 2025)
Background: Urinary tract infections (UTI) are among the most prevalent healthcare-associated infections (HAI), with E. coli and K. pneumoniae being the leading etiological agents. The increasing trend of antimicrobial resistance among these uropathogens threatens effective treatment, necessitating regular local surveillance. Therefore, the objective of this investigation is to assess the antibiotic resistance pattern among urinary isolates of E. coli and K. pneumoniae. Methods: A prospective observational study was conducted from January to April 2025 in the department of microbiology at Apollo Institute of Medical Sciences and Research, Hyderabad. A total of 305 non-duplicate urine samples from UTI patients were processed. Isolates of E. coli and K. pneumoniae were identified using standard microbiological procedures. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disc diffusion method according to CLSI guidelines. Results: Of the 305 samples, 88 (28.85%) were culture-positive for E. coli (60.2%) and K. pneumoniae (18.2%). E. coli isolates were predominantly recovered from patients aged 60–80 years and females (73.58%). K. pneumoniae was more frequent in the 20-40 years’ age group and also showed a female predominance (56.25%). High resistance was observed to third-generation cephalosporins, especially among E. coli. However, E. coli showed high susceptibility to fosfomycin (100%), nitrofurantoin (94%), and amikacin (92%). K. pneumoniae exhibited lower sensitivity overall, with highest susceptibility to amikacin (75%) and cotrimoxazole (75%). Conclusions: The study represents E. coli and K. pneumoniae as major uropathogens with concerning resistance patterns, particularly to third-generation cephalosporins. These findings reinforce the need for routine antimicrobial resistance monitoring and evidence-based empirical therapy to optimize UTI management.